every equations the the kind ax^2+bx+c=0 have the right to be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one as soon as ± is enhancement and one once it is subtraction.

You are watching: Factor x^2-2x+4

This equation is in standard form: ax^2+bx+c=0. Substitute 1 because that a, -2 because that b, and -4 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.

displaystylex=1pmsqrt5 Explanation: displaystylex^2-2x=4displaystylex^2-2x+1=4+1displaystyleleft(x-1 ight)^2=5displaystyleleft(x-1 ight)=pmsqrt5 ...
3x2-2x-4=0 Two solutions were discovered : x =(2-√52)/6=(1-√ 13 )/3= -0.869 x =(2+√52)/6=(1+√ 13 )/3= 1.535 step by step solution : step 1 :Equation in ~ the finish of action 1 : (3x2 - 2x) - 4 = 0 ...
6x2-2x-4=0 Two solutions were found : x = -2/3 = -0.667 x = 1 step by action solution : step 1 :Equation at the finish of step 1 : ((2•3x2) - 2x) - 4 = 0 action 2 : action 3 :Pulling out favor ...
-x2-2x-4=0 Two remedies were found : x =(2-√-12)/-2=1+i√ 3 = -1.0000-1.7321i x =(2+√-12)/-2=1-i√ 3 = -1.0000+1.7321i action by action solution : step 1 : step 2 :Pulling out favor terms : ...